Monitoring the heat-induced structural changes of alkaline phosphatase by molecular modeling, fluorescence spectroscopy and inactivation kinetics investigations - Dumitrașcu, Loredana (J Food Sci Technol, 2015)
The heat induced conformational changes of calf alkaline phosphatase (ALP) were analyzed using different methods, based on fluorescence spectroscopy, molecular modeling and inactivation studies. Experimental studies were conducted in buffer solution in the temperature range between 25 and 70 °C. Molecular dynamic (MD) simulation provided details on thermally induced changes in ALP structure, highlighting that heating favored the hydrophobic exposure and important alteration of the catalytic site above 60 °C. Additional information to MD data were obtained by using different fluorescence spectroscopy methods, which revealed a complex mechanism of thermal denaturation. Therefore, the emissive properties indicated an unfolding of ALP at temperatures below 60 °C, whereas at higher temperatures, the polypeptides chains fold leading to a higher exposure of Trp residues. In order to establish a structure-function relationship, the results were correlated with inactivation studies of ALP in buffer at pH 9.0. The inactivation data were fitted using a first-order kinetic model, resulting in an activation energy value of 207.26 ± 21.68 kJ · mol(−1).